A Novel Fusion Method by Static and Moving Facial Capture. (25th September 2013) - Liu, Shuai; Fu, Weina; Zhao, Wenshuo; Zhou, Jiantao; Li, Qianzhong
Abstract : For many years, face recognition has been one of the most important domains in pattern recognition. Nowadays, face recognition is more required to be used in video actually. So moving facial capture must be studied firstly because of performance requirement. Since classic facial capture method is not so suitable in a moving environment, in this paper, we present a novel facial capture method in a moving environment. Firstly, continuous frames are extracted from detecting videos by similar characteristics. Then, we present an algorithm to extract the moving object and restructure background. Meanwhile, with analysis of skin color in both moving and static areas, we use the classic faces capture method to catch all faces. Finally, experimental results show that this method has better robustness and accuracy.